Pyroelectric Harvesters for Generating Cyclic Energy - Chun-Ching Hsiao; Jia-Wai Jhang (Energies, 2015)
Pyroelectric energy conversion is a novel energy process which directly transforms waste heat energy from cyclic heating into electricity via the pyroelectric effect. Application of a periodic temperature profile to pyroelectric cells is necessary to achieve temperature variation rates for generating an electrical output. The critical consideration in the periodic temperature profile is the frequency or work cycle which is related to the properties and dimensions of the air layer; radiation power and material properties, as well as the dimensions and structure of the pyroelectric cells. This article aims to optimize pyroelectric harvesters by matching all these requirements. The optimal induced charge per period increases about 157% and the efficient period band decreases about 77%, when the thickness of the PZT cell decreases from 200 μm to 50 μm, about a 75% reduction. Moreover, when using the thinner PZT cell for harvesting the pyroelectric energy it is not easy to focus on a narrow band with the efficient period. However, the optimal output voltage and stored energy per period decrease about 50% and 74%, respectively, because the electrical capacitance of the 50 μm thick pyroelectric cell is about four times greater than that of the 200 μm thick pyroelectric cell. In addition, an experiment is used to verify that the work cycle to be able to critically affect the efficiency of PZT pyroelectric harvesters. Periods in the range between 3.6 s and 12.2 s are useful for harvesting thermal cyclic energy by pyroelectricity. The optimal frequency or work cycle can be applied in the design of a rotating shutter in order to control the heated and unheated periods of the pyroelectric cells to further enhance the amount of stored energy.